PENGARUH DANA PIHAK KETIGA, NON PERFORMING LOAN DAN INFLASI TERHADAP KREDIT YANG DISALURKAN OLEH LPD KABUPATEN BADUNG PERIODE TAHUN 2008 - 2012 - Sariasih, Ni Wayan; Dewi, Made Rusmala (E-Jurnal Manajemen; Vol 3 No 5 (2014), 2014)
ABSTRACT   LPD existence in the area can provide socioeconomic effect is very large for the weak in rural communities in general accordance with the function and purpose as a financial institution that collects funds from the public and channel them back in the form of loans . The purpose of this study was to determine the effect of Third Party Funds , Non Performing Loan ( NPL ) , and inflation simultaneously and partially and which variables are the most dominant influence on the amount of loans extended by LPD Badung regency period 2008-2012 . By using multiple linear analysis techniques menunnjukkan that simultaneously deposits , non -performing loans , and inflation significantly influence lending by LPD Badung regency . In parcial third-party funds and non -performing loans and the positive effect singnifikan while inflation has negative and not significant to the loans extended by the LPD Badung regency period 2008-2012 . The most dominant variables affect lending LPD Badung is variable deposits. Keywords : Number of loans disbursed , Third Party Funds , Non Performing Loan( NPL ) , and inflation
Keywords: Number of loans disbursed , Third Party Funds , Non Performing Loan( NPL ) , and inflation